Czynniki budujące reputację firmy - Głuszek, Ewa (Factors building the good reputation, 2005)
A good corporate reputation possesses the characteristics of an intangible asset and it may provide the corporation with a competitive advantage. It is vital for the success and survival of the firm in the long run, but it does not impact firm value, whereas corporate financial performance improves corporate reputation. A corporations image includes the perceptions of all stakeholders, but each of them has different needs - social and economical.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 135-144